Re-examining the Division of Candi Borobudur into Kāmadhātu, Rūpadhātu, and Arūpadhātu - So Tju Shinta LEE; Agus Aris Munandar; Lilawati Kurnia (SPAFA Journal)
The interpretation that Candi Borobudur is divided into kāmadhātu, rūpadhātu, and arūpadhātu is widely adopted in many writings about Borobudur, despite being questioned by some scholars. This paper analyses the narrative reliefs, the latticed stūpas of the three circular terraces, and the central stūpa of Borobudur to examine if they correlate with the three dhātus (realms of existence). Thematic narrative analysis was conducted to inquire the narrative reliefs in relation to key themes and subjects they represent. Comparative analysis was employed by comparing the key themes depicted on each group of narrative reliefs with the characteristics of each realm of existence. The findings suggest that the association of Borobudur with kāmadhātu, rūpadhātu, and arūpadhātu is problematic. There is no correlation between the narrative reliefs, the latticed stūpas of the three circular terraces, or the central stūpa with the three groups of dhātus. In terms of goals, the Lalitavistara and Gaṇḍavyūha-Bhadracarī aim for the highest and complete awakening (anuttara-samyak-sambodhi) by means of bodhisattva practices. The Gaṇḍavyūha-Bhadracarī discusses the dharmadhātu (realm of reality), the reality experienced by those who are awakened, which is beyond the three dhātus. As evidenced by its carvings and the sūtras they reference, Borobudur can be viewed as a roadmap with a gradual framework, depicting the mārga (path) towards Buddhahood within the bodhisattvayāna (bodhisattva vehicle). The findings of this research are expected to enhance the understanding of the Buddhist notions that underpinned the construction of Borobudur around the mid-8th to the early 9th century CE.